L’abord de la sexualité par les infirmier·es en oncologie. Quand le sentiment de légitimité s’articule aux effets de genre et d’âge - Marion Braizaz; Angélick Schweizer; Kevin Toffel (Genre, Sexualité et Société)
Gender norms play an important role in the way of nurses talk about sexuality with patients. Men and women are not equally informed about this subject and the informations they receive may significantly differ. However, this projection of different expectations between men and women does not sufficiently explain all the complexity of gender issues involved in the relationship between patient and care givers. In particular, age is important to take into account. Results based on in-depth interviews (5 men and 24 women) conducted with nurses working in oncology in Western Switzerland reveal gendered variability in patient care practices through the prism of aging. Moreover, it shows different effects on the way of talking about sexuality depending on “inter-gender” and “intra-gender” relationships and, also, specificities according to the age gap between nurses and patients. This gap allows to nuance the risk of an eroticisation in care givers’ and patients’ relationship seen as an obstacle to the discussion of sexuality in oncology.